Fair Valuation of a Renewable Energy Company in Indonesia - Fallery Fallery; Kin Tjendrasa (Jurnal Ilmiah Manajemen dan Bisnis, 2022)
Not only governments like Indonesia, but also many companies are eager to participate in the renewable energy sector to achieve their carbon neutral target due to the rise of environmental awareness. Mergers and acquisitions of the renewable company are opted by many companies to enter this new market. However, the buyer and the seller often experience disagreeable transaction value of the company, especially the value of the renewable company which does not have a long historical track record since renewable business is relatively new. DCF valuation method is applied to find the fair value of Alpha Co., a renewable energy company that could represent the new upcoming attractive market in Indonesia, renewable energy market. This study revealed that the fair value of Alpha Co. is USD 12.47 million with 10.74% and 10.76% of WACC in 2021 and after 2021 respectively. In addition, the sensitivity analysis proves the hypothesis about the significant influence made by the assumptions on which the most sensitive component could result in a 66.88% deviation from the original calculated firm value in this study.